A survey on children tracking system based on wearable localization techniques - Ahmed, Nadia; Gharghan, Sadik Kamel; Mutlag, Ammar Hussein (AIP conference proceedings, 2023)
Efficient children tracking schemes require attaching a wearable device to the target person or embedding a tracking software inside a handheld smartphone. Such schemes provide the person’s location and the path from source to destination. Therefore, the increasing interest in children tracking systems has led to a subsequent interest in wearable devices and Device-Free Localization (DFL) tracking systems. Mainly, many types of research were conducted on children tracking systems using different technologies and different types of wearable devices. Many novel ideas and approaches were developed regarding providing safety and supervision for children at home alone, on the roads to schools, or at other social events. Progress and results yielded in reviewed works were highly impressive. In this survey, a comprehensive overview of this evolutionary tracking system is provided to describe essential concepts and studies on Radio Frequency Identification (RFID), Bluetooth, Wireless Fidelity (Wi-Fi), Global System for Mobile Communication (GSM), Global Positioning System (GPS), and ZigBee wireless technologies. However, the main challenges faced by all types of tracking techniques are coverage area, location accuracy, power consumption, and computational cost. This survey is done in a structured manner, in which subjects are categorized according to the wireless technology used in tracking systems. Additionally, it discusses current obstacles within state-of-the-art children tracking systems.